Is it time to reclaim the "ethics" in business ethics education? - Jaganjac, Berina (Journal of business ethics, 2024)
This study explores the business ethics education literature published between 1982 and 2021. A systematic literature review and bibliometric analysis of 862 scholarly articles spanning 40 years of research on business ethics education revealed a thematic shift in the literature. Whereas older articles were predominantly concerned with ethics, relatively newer articles mainly focus on addressing the broader concept of sustainability. A content analysis of the 25 most locally cited articles between 1987 and 2012 identified two main research streams: (a) integration of business ethics into business school curricula and (b) the pedagogical approaches and tools used to teach business ethics. An additional content analysis of the 15 most locally cited articles published between 2016 and 2021 revealed that discussions related to integration and pedagogical approaches and tools were still ongoing in the literature, albeit with a focus on sustainability-related concepts such as the Sustainable Development Goals (SDGs) and the Principles for Responsible Management Education (PRME). Building upon our findings and existing literature, we develop a framework that we refer to as Transforming Ethics Education in Business Schools (TEEBS), which we argue may help business schools reclaim the ‘ethics’ in business ethics education.